Nexus between Capital Structure and Financial Performance of Nepalese Hydropower Companies - Lamichhane, Pitambar; Shrestha, Purna M. (Management Dynamics, 2021)
This study aims to shed light on the empirical investigation of the nexus between capital structure and financial performance. This paper focuses on hydropower companies listed on Nepal Stock Exchange (NEPSE) until mid-July 2020. This paper analyzes the nexus of capital structure with the financial performance of hydropower companies for the period 2005/06 to 2019/20. This study applies a descriptive and causal research design. Return on equity (ROE) is used to measure financial performance and is considered a dependent variable and short-term debt to capital (SDC), long-term debt to capital (LDC), total debt to capital (TDC), and debt to assets (DR) ratios are the measures of capital structure and used as explanatory variables. This paper reveals that short-term debt to capital ratio has a positive role in financial performance. Moreover, the findings of this paper depict that long-term debt to capital and total debt to capital has a significant positive impact on the financial performance of hydropower companies in Nepal. However, the debt to asset ratio inversely affects financial performance. Thus, this paper concludes that Nepalese hydropower companies should increase short-term, long-term, and total debt to capital ratios and decrease debt to assets to maximize financial performance. The implication of this study is in the formulation of optimal capital structure policy. The hydropower sector can apply the findings of this paper to formulate an appropriate capital structure policy to maximize its financial performance in Nepal.